2019
DOI: 10.1111/ijfs.14370
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal properties of β‐sitosterol‐beeswax‐sunflower oleogels

Abstract: Oleogels of b-sitosterol (Sit) and beeswax (BW) were combined at varying ratios (w/w) and added to sunflower oil (SFO) at concentrations of 10 g per 100 g and 20 g per 100 g oil to prepare oleogels (Sit/BW/ SFO). Structural and thermal properties were characterised and results showed that the hardness and enthalpy of oleogels were affected by the amount of b-sitosterol and beeswax in the oleogelator combination (Sit/BW, w/w). Oleogels with beeswax as the only oleogelator (Sit0/BW10) had the highest hardness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…As can be seen, the oleogels prepared with a low concentration (5%, w/w) of ST presented as independent or aggregated small crystal blocks with a small number of elongated needle‐like crystals. Studies have found that the oleogels formed based on sitosterol in sunflower seed oil have a long and branched fiber‐like network or needle‐like microscopic structure, which was similar to the results of the present study 22,50,51 . When the ST concentration was 7%, it was observed that the bulk crystals in RSO and FSO based oleogels became smaller, and the number of long needle‐like crystals also decreased.…”
Section: Resultssupporting
confidence: 90%
“…As can be seen, the oleogels prepared with a low concentration (5%, w/w) of ST presented as independent or aggregated small crystal blocks with a small number of elongated needle‐like crystals. Studies have found that the oleogels formed based on sitosterol in sunflower seed oil have a long and branched fiber‐like network or needle‐like microscopic structure, which was similar to the results of the present study 22,50,51 . When the ST concentration was 7%, it was observed that the bulk crystals in RSO and FSO based oleogels became smaller, and the number of long needle‐like crystals also decreased.…”
Section: Resultssupporting
confidence: 90%
“…In addition, it was also concluded that hardness value was increased when organogelator concentration was raised. The parallel result was also shown by Pang et al (2020). The authors found that the hardness of oleogel was dependent on organogelator concentration for different beeswax concentrations.…”
Section: Storage Stability Of Oleogelssupporting
confidence: 56%
“…Therefore, it should be noted that other ratios of the same mixture of oleogelator may produce oleogel with the enhanced properties of the oleogels prepared by the above‐explained oil types. β‐Sitosterol and beeswax combinations at different ratios in sunflower oil did not show any synergistic effect, and the monocomponent gel produced using the beeswax exhibited the highest strength and had a densely packed, spherical network, whereas the gel network formed by the sitosterol only had a needle‐shaped network (Pang et al., 2020).…”
Section: Methods Of Oleogelationmentioning
confidence: 99%
“…Using binary mixtures of wax shows the eutectic behavior of two waxes (Choi et al., 2020). Examples of most extensively studied waxes include sunflower wax (Barroso et al., 2020; Tavernier, Doan, et al., 2017a; Winkler‐Moser et al., 2019), rice bran wax (Tavernier, Doan, et al., 2017a), carnauba wax (Shuaishuai Yang et al., 2020), bees wax (Fayaz et al., 2017; Gómez‐Estaca et al., 2019; Martins et al., 2017; Pang et al., 2020; Ristanti et al., 2018; Winkler‐Moser et al., 2019), candelilla wax (Winkler‐Moser et al., 2019), berry wax (Barroso et al., 2020; Tavernier, Doan, et al., 2017a), and fruit wax (Okuro et al., 2018).…”
Section: Oleogelation and Oleogelsmentioning
confidence: 99%